(untitled) (Revista de Estudos da Linguagem, 2016)
Resumo: Esse artigo tem como perspectiva teórico-metodológica a Análise de Discurso de linha materialista. Seu objetivo é buscar historicidade e lugares de significação de documentos referenciais da política pública federal de Educação Ambiental e, assim, trazer contribuições da análise de discurso para a área de saber da educação ambiental. Os documentos analisados são o Tratado de Educação Ambiental para Sociedades Sustentáveis e Responsabilidade Global, o Programa Nacional de Educação Ambiental (ProNEA), e o Programa de Formação de Educadoras(es) Ambientais: por um Brasil educado e educando ambientalmente para a sustentabilidade (ProFEA). Procuramos dar visibilidade aos pré-construídos e condições de produção que sustentam esse discurso, e terminamos o trabalho apontando quais noções materialistas podem contribuir com a discussão e apropriação dos documentos da política pública de educação ambiental pelos coletivos que se relacionam com essa política. Palavras-chave: Educação Ambiental; Política Pública de Educação Ambiental; Análise de Discurso. Abstract: This article uses the materialistic conception of the Discourse Analysis as a theoretical and methodological perspective, based on authors such as Michel Pêcheux, Louis Althusser and Eni Orlandi, who are the authors that make up the conceptual framework of this field. The main goal of this article is to seek historicity and significance in federal documents of public policy for Environmental Education, thus bringing the discourse analysis to contribute to the area of environmental knowledge and education. The documents analyzed are the Treaty of Environmental Education for Sustainable Societies and Global Responsibility, the National Environmental Education Program (ProNEA), and the Environmental Educator Training Program: for an educated Brazil and educating for environmental sustainability (ProFEA). We have tried to give visibility to the pre-built and production conditions that sustain these discourses, and finished our work pointing out which materialistic notions can contribute to the discussion and appropriation of public policy documents on environmental education for groups that relate to this policy. Major brands and regularities found dealing with freedom and autonomy, and the contributions made relate to the notion of decentralization of the subject to understand how the discursive process takes place and its effects on production of subjectivity so as to affirm that the subject is not the source of his own speech. Keywords: Environmental Education; Public Policy on Environmental Education; Discourse Analysis.